Tolerant mechanism of model legume plant Medicago truncatula to drought, salt, and cold stresses - Zhang, Xiuxiu; Sun, Yu; Qiu, Xiao; Lu, Hai; Hwang, Inhwan; Wang, Tianzuo (Frontiers in Plant Science, 2022)
Legume plants produce one-third of the total yield of primary crops and are important food sources for both humans and animals worldwide. Frequent exposure to abiotic stresses, such as drought, salt, and cold, greatly limits the production of legume crops. Several morphological, physiological, and molecular studies have been conducted to characterize the response and adaptation mechanism to abiotic stresses. The tolerant mechanisms of the model legume plant Medicago truncatula to abiotic stresses have been extensively studied. Although many potential genes and integrated networks underlying the M. truncatula in responding to abiotic stresses have been identified and described, a comprehensive summary of the tolerant mechanism is lacking. In this review, we provide a comprehensive summary of the adaptive mechanism by which M. truncatula responds to drought, salt, and cold stress. We also discuss future research that need to be explored to improve the abiotic tolerance of legume plants.